Homicide and severe mental disorder: understanding and prevention - Farrell, Michael (Routledge, 2021)
"Homicide and Severe Mental Disorder: Understanding and Prevention provides a complete picture of how severe mental disorder can be assessed in cases of homicide, and how improved understanding can impact risk reduction and prevention. Michael Farrell brings together a wide range of material including theory, research, demographic data, case examples, enquiry reports, and practical strategies, providing clear examples throughout. Farrell draws on examples of homicide representing a great challenge to both comprehension and prevention - cases that have sometimes provoked media criticism of public policy and services and have aroused public anxiety. In seeking fuller understanding, the book takes an overview of severe mental disorder, homicide, and prevention, before introducing the approach of Situational Crime Prevention and related theory and discussing demographic features of perpetrators and victims. Turning to prevention, the text examines examples of research into homicides perpetrated by individuals with severe mental disorder. Insights from Situational Crime Prevention are applied to selected cases, and a wider view is then taken looking at the criminological features of means, motive, opportunity, and location. Organisational constraints and limitations of communication in services are considered, and cases illuminating the issues and challenges throughout the book are summarised in a structured end of volume glossary. As evidence and insights accumulate and cohere, they more clearly indicate preventive strategies. Homicide and Severe Mental Disorder will be of great interest to students, researchers and teachers in psychiatry, psychology, and criminology, health and mental health professionals, criminal justice personnel and those working with individuals with severe mental disorder"--